Semantic Mapping of the Names of Flora and Fauna at Danau Laut Mati Tasi Ana’ in Landu Dialect of Rote Language - Elvis Albertus Bin Toni; Yohanis Nurak Siwa; Imelda Tidora Sombo (Soshum: Jurnal Sosial dan Humaniora, 2021)
This study deals with the local names of floras and faunas living in the area of Danau Laut Mati Tasi Ana’ in Landu Sub District of Rote Regency. As language and physical nature are two inseparable entities, this study emphasizes that maintaining a language, to some extent, is equal to maintaining the existence of nature and vice versa. Documenting the names of floras and faunas in Landu Dialect of Rote Language and describing their meaning are two main purposes of this study. The underlying principle of it is to maintain the languge from being endangered. The main question that drives this study is to what semantic domain do the local names of floras and faunas belong to? In order to obtain data a Field observation was conducted. The photos of floras and faunas were taken. A native speaker of Landu dialect of Roti Languge who lives nearby the Lake wa consulted in order to get the local names of the floras and faunas. The data analysis follows the model presented by Suweta (2013). The data show that the floras and faunas living in the area of Danau Laut Mati Tasi Ana’ belong to four semantic domains i.e the domain of food for human being, food for animal, herb, and building material.